If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + -12x = -49 Solving -13 + -12x = -49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -12x = -49 + 13 Combine like terms: -13 + 13 = 0 0 + -12x = -49 + 13 -12x = -49 + 13 Combine like terms: -49 + 13 = -36 -12x = -36 Divide each side by '-12'. x = 3 Simplifying x = 3
| -13(a+4)=7(a+8) | | 6(4x-1)-2(x+1)=9(x+1) | | 25-8t/5 | | w+i=s/c | | 360=x+x-3+x+8+x-5 | | -4(3x+2)=18 | | 1/3x=57 | | -2x+1/2=-11/2 | | -.05x+15=10 | | 8g-12=23 | | -4=12-2w | | +22x(-1.6)= | | 4/5+5/12/1/4-2/3 | | 14-42= | | (y-8)-(y+4)=2y | | -15x=-4x+5 | | -p-24=28 | | (9x-2)-(-4x+6)= | | 2(x+4)+6=14 | | -9(x-4)-(x+1)=1 | | t/5+9=17 | | -2x+1=-13/2 | | 4x-4=2x | | 3(1)+2-1=5(1)-2(1)+1 | | k=1/2*.035*3.386*3.386 | | 1/3x=51 | | 8(2)+3=2(2) | | 21-7x=-63 | | -4(-4-5x)=-28-8x | | -2x+1/2=5/2 | | 13.7x-6.5=2.3x+9.3 | | -8+1=81+2 |